Simple method to derive aerosol microphysical properties from AERONET multiwavelength direct solar measurements - Otero, L. A.; Fochesatto, G. J.; Ristori, P. R.; Flamant, P. H.; Piacentïni, R. D.; Holben, B.; Quel, E. J. (Advances in Space Research, 2004)
International audience We present a simple method to retrieve aerosol optical properties from direct solar measurements obtained using sun-photometer measurements from AERONET (Aerosol Robotic Network). This monitoring program is a federation of ground-based remote sensing aerosol network conducted by NASA. The goal of this network is to assess the aerosol optical properties and to validate their retrievals with satellite information. Data from this collaboration provide globally distributed observations of spectral aerosol optical thickness, precipitation water, and aerosol volume size distribution (derived from the inversion products) in geographically diverse aerosol regimes. In this work, we present a simple method to deduce the aerosol microphysical properties in the sub-micrometer radius range, which were derived from the aerosol optical thickness measurements using Mie kernel functions with a proposed synthetic radius spectrum. Results and comparison of this inversion procedure with other standard inversion products are shown for Buenos Aires (CEILAP) and Córdoba (CETT) sites of AERONET network.